Surgical outcomes after pediatric kidney transplantation at the University of Heidelberg - Mehrabi, Arianeb; Golriz, Mohammad; Khajeh, Elias; Ghamarnejad, Omid; Kulu, Yakup; Wiesel, Manfred; Müller, Thomas; Majlesara, Ali; Schmitt, Claus P.; Tönshoff, Burkhard (Journal of pediatric urology, 2019)
Background - Kidney transplantation (KTx) is the treatment of choice for children with end-stage renal disease (ESRD). - Objective - An update of 48 years of surgical experience with pediatric KTx (PKTx) is presented, and the results between recipients of organs from deceased donors (DDs) and living donors (LDs) are compared. - Study design - All patients younger than 18 years who underwent KTx between 1967 and 2015 were evaluated. Data from 540 PKTx operations (409 DD and 131 LD) were obtained from the transplant center database. Peri-operative data and graft and patient survival were analyzed in the DD and LD groups. - Results - Fewer recipients in the LD group underwent dialysis before PKTx than those in the DD group (50.8% in LD vs. 94.9% in DD, P < 0.001). The mean duration of dialysis (DD: 798 ± 525 days vs. LD: 625 ± 650 days, P = 0.03), time on the waiting list (DD: 472 ± 435 days vs. LD: 120 ± 243 days, P < 0.001), cold ischemia time (CIT) (DD: 1206 ± 368 min vs. LD: 140 ± 63 min, P < 0.001), operation time, and hospital stay were lower in the LD group. Except for arterial stenosis, the rates of postoperative vascular and urological complications were not different between the two groups. The cumulative 25-year graft and patient survival rates were 46.4% and 84.1% in the DD group and 76.5% and 96.1% in the LD group, respectively. - Discussion - PKTx is the treatment of choice for children with ESRD. Graft quality has a direct impact on KTx outcome and rate of graft failure. Better HLA compatibility and shorter CIT reduce the impairment of graft function after LD PKTx. In addition, Establishment of an interdisciplinary approach using an individualized risk assessment and prevention model can improve PKTx outcomes. - Conclusion - Compared with DD PKTx, LD PKTx has better graft survival associated with a shorter duration of preceding dialysis, waiting time, and CIT and seems to be more beneficial for children.Image 1
Available online 24 January 2019
Gesehen am 25.02.2020